Nonlinear dynamics in menu cost economies? Evidence from U.S. data - Andrés Blanco; Corina Boar; Callum Jones; Virgiliu Midrigan (Federal Reserve Bank of Atlanta, 2024)
We show that standard menu cost models cannot simultaneously reproduce the dispersion in the size of micro-price changes and the extent to which the fraction of price changes increases with inflation in the U.S. time-series. Though the Golosov and Lucas (2007) model generates fluctuations in the fraction of price changes, it predicts too little dispersion in the size of price changes and therefore little monetary nonneutrality. In contrast, versions of the model that reproduce the dispersion in the size of price changes and generate stronger monetary nonneutrality predict a nearly constant fraction of price changes.
Keywords: E31; E32; E52; 330; menu costs; inflation; fraction of price changes